The Impact of Hangeshashinto on Symptoms and Gut Microbiota in Diarrhea-type Irritable Bowel Syndrome: A Retrospective Analysis - Naohisa Yoshida; Takeshi Yasuda; Yoshikazu Inagaki; Daisuke Hasegawa; Kohei Fukumoto; Takaaki Murakami; Ryohei Hirose; Osamu Dohi; Kazuhiko Uchiyama; Tomohisa Takagi; Yoshito Itoh (Journal of the Anus, Rectum and Colon)
Objectives: Effective treatments for diarrhea-type irritable bowel syndrome (IBS-D) are limited. Hangeshashinto (HST), an anti-inflammatory Kampo medicine, may offer benefits but its efficacy for IBS-D requires further investigation. This study evaluated IBS-D symptom improvement and gut microbiota changes following HST administration. Methods: This was a multicenter retrospective study with a prospective analysis of microbiota conducted at five affiliated institutions. Patients diagnosed with IBS-D based on the ROME IV criteria between April 2019 and December 2023, who received HST 7.5 g/day for 2-3 weeks were included. The outcome measures were improvement rates in overall symptoms, stool frequency, stool consistency, and abdominal pain. Intestinal microbiota was analyzed using 16S rRNA gene sequencing from fecal samples of 20 patients before and after HST treatment. Results: One hundred patients (42 males/58 females, mean age: 69.5±11.8 years) were analyzed. The overall improvement rate of HST was 82.0%. Those of males and females were 81.0% and 82.8% (p=0.816). By age, those of patients aged 75 and aged <75 years were 82.9% and 81.5% (p=0.869). The improvement rates of stool frequency, stool consistency, and abdominal pain were 59.0%, 51.0%, and 62.0%, respectively. The stool frequency per week before and after HST was 21.7±18.2 vs. 14.0±12.6 (p<0.001). Significant differences in gut microbiota β diversity were observed, although α diversity was not significantly changed. Bacteroides (p=0.003) and Ruminococcus (p=0.010) decreased significantly, while Megasphaera (p=0.030) and Subdoligranulum (p=0.002) increased. Conclusions: HST may improve IBS-D symptoms by altering microbiota composition.